2023
DOI: 10.1038/s41420-023-01315-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying CDC7 as a synergistic target of chemotherapy in resistant small-cell lung cancer via CRISPR/Cas9 screening

Abstract: There is currently a lack of efficacious treatments for patients with chemo-resistant small-cell lung cancer (SCLC), leading to poor prognoses. We examined a chemo-resistant SCLC cell line using genome-wide CRISPR/Cas9 screening and identified serine/threonine kinase cell division cycle 7 (CDC7) as a potential synergistic target. Silencing CDC7 in chemo-resistant SCLC cells decreased the IC50 and improved the efficacy of chemotherapy. Based on the highest single agent model, the CDC7 inhibitor XL413 had a syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Cell division cycle 7 (CDC7) was identified by Deng. et al using CRISPR/Cas9 screening ( Deng et al, 2023 ). In chemo-resistant small cell lung cancer, CDC7 possibly acts as synergistic target ( Deng et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell division cycle 7 (CDC7) was identified by Deng. et al using CRISPR/Cas9 screening ( Deng et al, 2023 ). In chemo-resistant small cell lung cancer, CDC7 possibly acts as synergistic target ( Deng et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
“…et al using CRISPR/Cas9 screening ( Deng et al, 2023 ). In chemo-resistant small cell lung cancer, CDC7 possibly acts as synergistic target ( Deng et al, 2023 ). Studies revealed that suppressing CDC7 lowered the IC50 and increased chemotherapy effectiveness in chemo-resistant SCLC cells ( Deng et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRISPR/Cas9 screening in chemo-resistant small-cell lung cancer (SCLC) identified serine/threonine kinase cell division cycle 7 (CDC7) as a potential synergistic target. Combination of CDC7 inhibitor XL413 and chemotherapy led to apoptosis of chemo-sensitive SCLC in xenograft tumor [ 132 ]. Acute Myeloid Leukemia (AML) cell lines such as MOLM-13, MV4-11, HL-60, OCI-AML2, OCI-AML3 were examined for therapeutic targets via genome-wide CRISPR screening, indicating KAT2A inhibition as a therapeutic strategy in AML [ 133 ].…”
Section: Crispr Screening Application In Cancer Therapymentioning
confidence: 99%
“…A genome-scale CRISPR/Cas9 deletion screen in DDP- and VP16-treated and untreated resistant SCLC cells results in the identification of the serine/threonine kinase cell division cycle 7 (CDC7) as a promising target for chemotherapeutic synergy. The combined use of CDC7 inhibitors and other drugs helps to overcome chemoresistance in the treatment of SCLC and improves patient prognosis ( Deng et al, 2023 ). A human-genome-wide library was employed to screen the genes necessary for CHK1i sensitivity in lung cancer cells, and several MMB-FOXM1 complex components were discovered ( Branigan et al, 2021 ).…”
Section: Application Of Crispr Screens In Lung Cancer Treatmentmentioning
confidence: 99%